Quantitative Analysis of the Global Proteome in Peripheral Blood Mononuclear Cells from Patients with New‐Onset Psoriasis. Issue 19 (5th September 2018) - Li, Fengdi; Wang, Yacui; Li, Yu; Yang, Hongpu; Wang, Hongmei
Abstract: Psoriasis is a common chronic autoimmune skin disease involving the activation of T cells. To explore the proteomic signature of peripheral blood mononuclear cells, a quantitative analysis of their global proteome was conducted in samples from Chinese patients with new‐onset psoriasis ( n = 31) and healthy controls ( n = 32) using an integrated quantitative approach with tandem mass tag labeling and LC–MS/MS. Protein annotation, unsupervised hierarchical clustering, functional classification, functional enrichment and cluster, and protein–protein interaction analyses were performed. A total of 5178 proteins were identified, of which 4404 proteins were quantified. The fold‐change cutoff was set at 1.2 (patients vs controls); 335 proteins were upregulated, and 107 proteins were downregulated. The bioinformatics analysis indicated that the differentially expressed proteins were involved in processes related to the activation of immune cells including the nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) pathway, cellular energy metabolism, and proliferation. Three upregulated proteins and two phosphorylated proteins in the NF‐κB pathway were verified or identified by Western blotting. These results confirm that the NF‐κB pathway is critical to psoriasis. In addition, many differentially expressed proteins identified in this study have never before been associated with psoriasis, and further studies on these proteins are necessary.